Practical efficiency the new method of staining wet stool smears for the microscopic detection of intestinal protozoan parasites - Kyrychenko , Igor; Pokhil, Sergiy; Tymchenko, Olena; Krestetska , Svitlana (Annals of Mechnikov's Institute, 2023)
Introduction. Until now, intestinal protozoan infections (IPIs) cause a significant socio-economic burden and are a recognized problem for health care in all countries of the world. In the economically developed countries of Europe and Ukraine, IPIs are most often caused by Blastocystis sp. (formerly Blastocystis hominis, the causative agent of blastocystosis), Dientamoeba fragilis (the causative agent of dientamoebiasis), Giardia lamblia (synonymous names - G. intestinalis, G. duodenalis, the causative agent of giardiasis) and Cryptosporidium spp. (most often species C. parvum and C. hominis, the causative agent of cryptosporidiosis), while protozoan intestinal invasions of other etiology are relatively rare. Stool microscopy methods, due to technical availability and relative cheapness, remain the most widely used in the laboratory diagnosis of IPIs in all countries of the world. The effectiveness of microscopic detection of disease-causing protozoan parasites in stool depends primarily on the smear staining method, which should provide reliable visualization of the characteristic features in stained parasite cells for their identification and differentiation from morphologically detailed "artifacts" that are often present in feces (such as: yeast-like fungi, leukocytes, macrophages, erythrocytes, fat droplets, spores, kernel shells and other plant detritus). The traditional algorithm of microscopic analysis of feces (native, preserved and concentrated by flotation or sedimentation) for detection of Blastocystis sp., D. fragilis, G. lamblia and Cryptosporidium spp. is technically burdensome, resource-, labor- and time-consuming. This algorithm provides for simultaneous (parallel) preparation of three smears from the same stool sample. Namely: one wet smear temporarily stained with iodine dye (1% solution Lugol's, D'Antoni's, Dobell's, etc.) and two smears fixed, permanently stained, one of which Wheatley's modification trichrome (or Heidenhain's iron-hematoxylin) method, and the other by the modified (cold) Ziehl-Neelsen method. The goal of this study was to determine the practical effectiveness (diagnostic performance, resource-, labor- and time-consuming) of the new method of semi-permanently staining (with dye betaiod-fast green-glycerol) wet fecal smears for the microscopic detection of intestinal protozoan parasites in comparison with a group of traditional methods staining which are used for the same purpose. Materials and Methods. Microscopic examination of 160 preserved (10% formalin solution) stool samples (each of which was a triple-faeces-test) of military personnel with gastrointestinal symptoms was performed (hereafter referred to as MILPERS). Stool samples were taken during the period of inpatient medical care for MILPERS (February-July 2023) in the infectious diseases department of the Military Medical Clinical Center of the Northern Region of the Ministry of Defense of Ukraine. The algorithm for microscopic examination of stool samples included the following procedures: concentration of samples by formalin-ethyl acetate sedimentation; preparation of four types of smears from each concentrated pellet, namely - wet smear semi-permanently stained with the new betaiod-fast green-glycerol dye, wet smear temporarily stained with 1% solution Lugol's, two smears permanently stained, one of which Heidenhain's iron-hematoxylin (or Wheatley's trichrome), and the other by the modified Ziehl-Neelsen method; microscopic examination of stained smears under conditions of appropriate magnification and visual identification of detected intestinal protozoan parasites by their inherent morphological features and tinctorial properties. The practical efficiency of the new method of semi-permanently staining wet fecal smears for the microscopic detection/identification of protozoan parasites and a group of traditional staining methods of a similar purpose was evaluated according to the criteria diagnostic performance, resource-, labor- and time-consuming. Indicators of diagnostic performance are the actual values of microscopic detection/identification of intestinal protozoa in 160 stool samples of MILPERS, determined by the parallel use of the new method and traditional methods of staining their smears, while indicators of resource-, labor- and time-consuming were obtained by the method of analytical calculation of microscopic examination of one stool sample for intestinal protozoan parasites using comparable staining methods. Results and Discussion. According to the results of a microscopic study of 160 stool samples from MILPERS of the Northern Region of Ukraine, we found that the general level of infestation of these MILPERS with intestinal protozoa reaches 11.3%, among which the specific weight of protozoan monoinvasions (with one type of parasite) is 72.2%, and mixinvasions (with several types of parasites) is 27.8% %. The spectrum of intestinal protozoan parasites detected at MILPERS includes pathogenic (Blastocystis sp., D. fragilis, G. lamblia) and commensally (Chilomastix mesnili, Iodamoeba butschlii) species. In 75% of MILPERS infected with pathogenic protozoan, IPIs were diagnosed with mild to moderate clinical severity. Worm infestations were not detected in the examined MILPERS. The new method of semi-permanently staining wet fecal smears with betaiod-fast green-glycerol dye showed universal suitability for the microscopic detection of the entire spectrum of intestinal protozoan parasites present in the examined stool samples. The use of betaiod-fast green-glycerol dye provides a sufficiently clear, contrasting and polychrome staining of the cells of pathogenic protozoa - Blastocystis sp., D. fragilis and G. lamblia, which allows them to be reliably detected/identified by their shape, size, structural elements and tinctorial properties during the microscopy of fecal smears. For indicators of the microscopic performance detection of intestinal diseases in stool, the new method of semi-permanently staining wet fecal smears in general is not compromised by the three methods of the traditional algorithm of their preparation (with staining 1% solution Lugol's, Heidenhain's iron-hematoxylin or Wheatley's trichrome and modified Ziehl-Neelsen method). Fechner's correlation coefficient (Kf) between groups of positive results of microscopic detection/identification of intestinal protozoa in stool samples from MILPERS, obtained using the new and traditional smear staining methods was +1. At the same time, the new method of semi-permanent staining of wet fecal smears reliably outperforms the usual method of staining them with 1% Lugol's solution (р < 0.05) in terms of the ability to visually identify the dominant pathogens of IPIs - Blastocystis sp. and D. fragilis, whose specific share in the etiological spectrum of protozoan pathogens in MILPERS totaled 87.5%. Based on the results of the analytical calculation, the values of the indicators of the practical effectiveness of the microscopic examination of one stool sample using a new method of smear staining were determined, which are: resource consumption (the cost of reagents needed to produce a consumable amount of working dye solutions in UAH) - 2.5; labor intensity (absolute quantity of necessarily performed procedures from the beginning of smear production to the end of its microscopic view) – 6; time-consumption (total duration of mandatory procedures from the beginning of the preparation of the smear to the end of its microscopic view in mins) – 25. Conclusion. The new method of staining wet stool smears with betaiod-fast green-glycerol dye provides sufficiently clear, contrasting and polychrome staining of Blastocystis sp., D. fragilis and G. lamblia, which allows microscopically to reliably detect/identify them in the examined feces. The practical effectiveness of the new method of smear staining according to the criterion of diagnostic performance of detection/identification of pathogenic protozoan parasites in stool is not inferior to traditional staining methods of a similar purpose and, compared to the latter, is characterized by lower resource consumption (by 7.4 times), labor intensity (by 4.8 times) and time-consumption (in 7.6 times).